The cyclicality of fiscal policy in South Asia - Zakaria, Muhammad; Junyang, Xi (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The paper empirically analyses the role of macroeconomic, political and institutional variables in determining cyclical patterns of government revenues, expenditures and fiscal balance in South Asian Countries (SACs). Panel regression analysis is conducted for the period 1980 to 2013. The findings support existing literature about developing countries demonstrating that fiscal policies are strongly procyclical in SACs and there is significant evidence of persistence. Revenues have decreased and expenditures have increased with output cycle which has deteriorated the fiscal balance. This indicates that fiscal balance is procyclical with output cycle in SACs and this procyclicality increases during good times. The results suggest that SACs can conduct counter cyclical fiscal policies if they stabilize output, control inflation and structural shocks, have deep financial markets, high financial openness, have few veto players in the political procedures and have stronger institutions. These results are robust to alternative measures of output cycle and model specifications
Argumenta Oeconomica, 2015, Nr 1 (34), s. 33-60
Keywords: fiscal policy; cyclicality; volatility